Notes on metus lymphaticus at seneca (epist. 13,8 f.) and Lucan (1,466-522) Zum Motiv des metus lymphaticus bei Seneca (epist. 13,8 f.) und Lucan (1,466-522) - Diez, Christopher (Hermes, 2021)
Both, Lucan and Seneca refer to the Stoic concept of metus lymphaticus; whereas Seneca intends to warn his readers of the negative outcome of irrational panic, Lucans illustrates its disastrous consequences. In this paper, focus is thus brought to their similarities, and especially to their different presentations and purposes.
CRIS-Team Scopus Importer:2021-05-28
Keywords: Epic indignation; Lucan; Metus lymphaticus; Philosophical therapy; Philosophy and literature; Seneca